Retour au travail après une lésion professionnelle : étude de cas sur les effets du droit sur l’expérience des justiciables - Katherine Lippel; Camille Lanthier-Riopel (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article reports on findings drawn from a Quebec study investigating the experiences of precariously employed or mobile workers who attempt to return to work after a work injury. It illustrates the unexpected effects of legal regulations and their associated economic incentives on the return-to-work process. Analyzing the legal context of three case studies drawn from interviews with 11 injured workers and 18 key informants, the study examines the ways in which the regulatory framework may shape the claimants’ experiences. It first provides a detailed account of the return-to-work experiences of three workers: a fly-in, fly-out health care worker and two employees of temporary employment agencies. It then provides an in-depth examination of the mechanisms by which specific parameters of the regulatory framework that governs workers’ compensation, occupational health and safety, and the right to equality shape events leading to less than satisfactory outcomes in disability prevention. The study shows that the experiences of the three injured workers were shaped by regulatory issues that had unforeseen consequences. Avenues are suggested to improve the regulatory effectiveness of laws designed to prevent work disability.